Utilización integral en la industria papelera de las pulpas al sulfato de 2 especies de eucaliptos - Plasencia Becerra, Alvaro Daniel (2009)
The species object of this study, The Eucalyptus Globulus Labilly Eucaliptus Grandis were chosen for this purpose considering: its greater abundance in relation to other species of Eucalyptus and hardwoods existing in the country, its rapid growth and its higher volumetric yield per hectare. All the Eucalyptus species tested come from the Cuzco area, which at the trial of the Foresters offer the best climatic conditions for the growth of these species. Pinus radiata splinters were shipped from Canada in hermetically sealed bags. To obtain the pulps, the sulphate process was used, also called Kraft, and the cellulose pulps were then bleached through a scheme or CEDA sequence. (Chlorination, Extraction, Dioxidation). For the technical evaluation and subsequent comparison of these Eucalyptus, the main parameters of the digestion were kept constant, such as% sulphidity, active Alkali, cooking temperatures and liquor ratio, wood, only the cooking time was left at maximum temperatures (T. of Cooking) to obtain the same degree of delignification. Also during bleaching, the same conditions were maintained for all samples. During the defibration or refining to which the pulps were subjected, different refining times were used in order to observe at what times the best pulp characteristics of the pulp are obtained and to evaluate in some way the energy consumption they originate. Unbleached and bleached cellulose pulps were analyzed in terms of whiteness, opacity and physical-mechanical resistances. The yields, amount of rejections and No. Kappa of the celluloses were also determined. The results obtained indicate that all the studied species of Peruvian Eucalyptus are suitable to a greater or lesser degree for the production of pulp cellulose for paper